(untitled) (Research, Society and Development, 2024)
Understanding the surgical strategies available for the management of multiple injuries is essential for healthcare professionals involved in the treatment of these patients. Therefore, the justification for this research lies in the complexity and severity of these cases, which often present significant challenges to health professionals. Multiple injuries result from a variety of traumatic events, such as automobile accidents and sports trauma, and can affect different systems of the human body. A systematic review of the literature was carried out, through a survey of data in scientific databases: LILACS and PUBMED. Surgical strategies for the management of multiple injuries represent a constantly evolving field, marked by a variety of surgical approaches and techniques. From this review, it is evident that there is no single universally applicable approach, but rather a need to personalize treatment based on the individual characteristics of each patient and the circumstances of the trauma. The different surgical strategies discussed, such as "Damage Control Surgery", sequential approach, minimally invasive surgery and tissue reconstruction techniques, offer valuable options for surgeons to face the challenges presented by multiple injuries. The results found show that the choice of the appropriate surgical approach for each patient must be based on a comprehensive assessment of the injuries present, the patient’s clinical condition, as well as considerations about the experience and availability of resources of the surgical team. A multidisciplinary and collaborative approach is essential to ensure the best possible outcome for patients with multiple injuries.